Quality and sensory characteristics of local commercial peanut butter - Cortez, Maricar Pabustan; Francisco, Ma. Leonora dL. (2006)
ABSTRACT Ten local commercial peanut butter samples were evaluated for quality and sensory characteristics. Parameters tested include color evaluation using the Hunter Lab colorimeter and fat determination using the Soxhlet method. Sensory evaluation was done using the line marking test and the 9-point hedonic scale rating. Sample 2932 obtained the lightest color with a mean Hunter Lab L value of 71.81 while sample 5879 was the darkest with a mean L value of 47.58. Sample 2808 contained the highest percentage of crude fat at 51.33% while sample 6551 gave the lowest percentage of crude fat at 37.72%. Sensory evaluation indicated variability between the samples for all the characteristics tested. Using the 9-point hedonic scale, sample 6392 was regarded as the most acceptable product in terms of color, aroma, flavor, sweetness, consistency and spreadability. The respondents generally prefer peanut butter with brown color, distinct peanut aroma and flavor, right sweetness (not bland but not too sweet), and with right consistency and spreadability (not too thin to spread and not sticky).
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut butter